Application of adjustable broadband sound absorption aerogel in noise reduction
By mixing aramid nanofibers with magnetic particles and using them in a magnetic field, an adjustable wide frequency acoustic aerogel is prepared, which solves the problem of limited optimization of sound absorption performance in noise reduction by existing aerogel materials, and realizes the The feasibility of efficient acoustic wave absorption and industrial production of aerogels.
Patent Information
- Application Number
- CN202411631055.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-18
AI Technical Summary
In terms of noise reduction, existing aerogel materials have problems such as limited sound absorption performance optimization, large material density, large volume, poor absorption intensity and complex preparation process, and cannot further release their sound absorption performance.
By mixing aramid nanofibers with magnetic particles, an adjustable wide frequency acoustic aerogel is prepared and the aerogel is used in the magnetic field for sonic absorption. The method includes mixing the aramid nanofiber dispersion with magnetic particles and preparing an aerogel with an enlarged micropore diameter and a rough microscopic surface through a freeze-drying process.
The microscopic surface roughness and pore size of the aerogel are increased, and its impedance matching effect on sound waves and low-frequency sound absorption performance are improved. The process is simple and the cost is low, which is suitable for industrial mass production.
Smart Images

Figure CN119463277A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sound wave absorption, relates to a sound wave absorption method, and in particular to an application of an adjustable broadband sound-absorbing aerogel in noise reduction. Background Art
[0002] Aerogel materials have begun to be used in noise protection systems for aviation and aerospace equipment. With the rapid development of aviation and aerospace equipment, researchers not only consider the stability of noise reduction in the design of related equipment, but also begin to pay attention to the controllability of noise reduction. Therefore, the development of noise reduction materials or structures that are both excellent and controllable will further improve the comprehensive performance of aerospace equipment. However, the current work on structural design for optimizing the sound absorption performance of aerogels is still limited to the microstructure size, and the sound absorption performance of aerogels cannot be further released. In addition, multifunctional aerogel materials for sound absorption still have defects such as high material density, large material volume, poor absorption strength, or complex preparation process.
[0003] The invention patent application with publication number CN 114920978A discloses a method for preparing an aerogel with both electromagnetic shielding and sound absorption functions: by doping Ti3C2T in aramid nanofiber aerogel x MXene and polyimide realize the structural design of the open-pore structure and porosity of aerogel. Although the invention realizes the enhancement of the low-frequency sound absorption performance of aerogel, it does not increase the microscopic surface roughness of aerogel, and thus cannot further improve the sound absorption performance of aerogel. In addition, the preparation process of the invention is complicated and not convenient for industrial mass production. The invention patent application with publication number CN116758887A discloses a sound absorption system based on acoustic metamaterials and its control method: based on thermally responsive shape memory polymers and by adding magnetic particles, the magnetic response shape memory performance of acoustic metamaterials is realized. Although the invention realizes the controllability of sound absorption performance, it has defects such as narrow sound absorption bandwidth and large structural size. Summary of the invention
[0004] The present invention provides an application of an adjustable broadband sound-absorbing aerogel in noise reduction to overcome the defects of the prior art.
[0005] To achieve the above object, the present invention adopts the following technical solutions:
[0006] The invention discloses an application of an adjustable broadband sound-absorbing aerogel in noise reduction: placing the broadband sound-absorbing aerogel in a magnetic field to absorb sound waves; the preparation method of the broadband sound-absorbing aerogel comprises the following steps: step 1, mixing and stirring an aramid nanofiber dispersion with magnetic particles to obtain an aramid nanofiber / magnetic particle mixed solution; step 2, freeze-drying the aramid nanofiber / magnetic particle mixed solution to obtain an aramid nanofiber / magnetic particle mixed aerogel.
[0007] To optimize the above technical solutions, the specific measures taken also include:
[0008] Furthermore, the intensity of the magnetic field is 0.1-2T.
[0009] Furthermore, the magnetic field is generated by a copper coil connected to a DC power supply.
[0010] Furthermore, in step one, the preparation method of the aramid nanofiber dispersion is: mixing aramid fibers, potassium hydroxide, deionized water and dimethyl sulfoxide for 6 to 8 days to crack the aramid fibers to obtain aramid nanofibers; and then dispersing the aramid nanofibers in deionized water to obtain the aramid nanofiber dispersion.
[0011] Furthermore, in the preparation of the aramid nanofiber dispersion, the usage ratio of aramid fiber, potassium hydroxide, deionized water and dimethyl sulfoxide is 0.5-2g: 0.5-2g: 1-3g: 300-800ml, preferably 1g: 1g: 2g: 500ml.
[0012] Furthermore, in step one, the magnetic particles are ferrite, carbonyl iron powder or iron-silicon alloy.
[0013] Furthermore, in step one, the concentration of the aramid nanofiber dispersion is 1-3 mg / g, preferably 2 mg / g; the mass ratio of the aramid nanofiber dispersion to the magnetic particles is 100-200:0.3-1.0, preferably 160:0.64.
[0014] Furthermore, in step 1, the stirring time is 3 to 5 hours and the rotation speed is 1000 r / min.
[0015] Furthermore, in step 2, the freeze-drying temperature is -10 to -80°C and the time is 5 to 7 days.
[0016] Furthermore, in step 2, before freeze drying, the aramid nanofiber / magnetic particle mixed solution is first frozen at -18 to -80°C for 24 hours.
[0017] The beneficial effects of the present invention are as follows: the present invention provides an application of an adjustable broadband sound-absorbing aerogel in noise reduction. The broadband sound-absorbing aerogel is doped with magnetic particles, which gives it a magnetic response property, and can achieve broadband regulation of sound absorption performance based on a magnetic field, thereby achieving efficient absorption of sound waves in a magnetic field. Specifically, aramid fibers and magnetic particles are used as raw materials, and a hybrid aerogel structure with an enlarged microscopic pore size and a rough microscopic surface is designed and constructed through a freeze-drying process. The hybrid aerogel structure design method has a simple process and low cost, and is more conducive to industrial mass production; magnetic particles are used as fillers to effectively increase the microscopic pore size and microscopic surface roughness of the aerogel, thereby achieving the impedance matching effect of the aerogel for sound waves and enhancing the low-frequency sound absorption performance. In addition, the broadband sound-absorbing aerogel can have both high thermal stability and low thermal conductivity, which is of great significance for the noise reduction needs in complex environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 is a scanning electron microscope image of the broadband sound-absorbing aerogel prepared in Example 1;
[0019] Figure 2 are photos of the magnetic field generating devices of Example 1 and Comparative Example 3;
[0020] Figure 3 1 is a graph showing the test results of the sound wave absorption performance of Comparative Example 1 and Comparative Example 3;
[0021] Figure 4 1 is a graph showing the test results of the sound wave absorption performance of Example 1 and Comparative Example 1;
[0022] Figure 5 1 is a graph showing the test results of the sound wave absorption performance of Comparative Example 2 and Comparative Example 3;
[0023] Figure 6 is an optical microscope image of the aramid nanofiber / magnetic particle hybrid aerogel structure with and without a magnetic field;
[0024] Figure 7 is an optical microscope image of the aramid nanofiber aerogel structure with and without a magnetic field;
[0025] Figure 8 Schematic diagram of the deformation of the aramid nanofiber / magnetic particle hybrid aerogel structure with and without a magnetic field. DETAILED DESCRIPTION
[0026] The present invention is further described below in conjunction with specific embodiments.
[0027] Example 1
[0028] This embodiment provides an application of a controllable broadband sound-absorbing aerogel in synergistic with a magnetic field in noise reduction: the broadband sound-absorbing aerogel is placed in a magnetic field to absorb sound waves.
[0029] The preparation method of broadband sound-absorbing aerogel comprises the following steps:
[0030] Step 1: Take 1g of aramid fiber, 1g of potassium hydroxide and 2g of deionized water, add them into 500ml of dimethyl sulfoxide, stir for one week to decompose the aramid fiber to form aramid nanofibers, and wash them repeatedly with deionized water to obtain aramid nanofibers. Then disperse the aramid nanofibers in deionized water to obtain a 2mg / g aramid nanofiber solution.
[0031] 160 g of aramid nanofiber solution and 0.64 g of carbonyl iron powder were mixed and stirred for 4 hours to obtain an aramid nanofiber / magnetic particle mixed solution.
[0032] Step 2: Vacuum filter the aramid nanofiber / magnetic particle mixed solution to 32 g, fill it into a prefabricated square mold of 4 cm*4 cm*2 cm, and move it to a refrigerator and freeze it at -18°C for 24 hours.
[0033] The frozen aramid nanofiber / magnetic particle mixed solution was transferred to a vacuum freeze dryer for freeze drying at a cold well temperature of -80°C for 7 days, and finally an aramid nanofiber / magnetic particle mixed aerogel was obtained. The microscopic surface roughness of the broadband sound-absorbing aerogel is shown in the attached figure. Figure 1 shown.
[0034] like Figure 2 As shown, the magnetic field is generated by a copper coil with a DC power supply. The copper wire diameter is 0.6 mm, the inner diameter of the coil is 60 mm, the outer diameter of the coil is 65 mm, the coil height is 50 mm, the number of coil turns is 304, the allowable current at room temperature is 5.5 A, the current of the DC power supply is 2 A, and the magnetic field strength generated is 0.2 T.
[0035] Sound wave absorption performance test: Add the following on the outside of the four-channel digital signal acquisition system and the impedance tube: Figure 2 The magnetic field generating device was used to measure the sound absorption performance at 1600-6300Hz, and the magnetic field intensity was 0.2T. The results are as follows Figure 4 shown.
[0036] Comparative Example 1
[0037] This comparative example provides an application of aerogel in noise reduction: the aerogel is directly used for sound wave absorption. The preparation method of the aerogel is the same as that of the embodiment.
[0038] Sound wave absorption performance test: Using a four-channel digital signal acquisition system and an impedance tube, the sound absorption performance was measured at 250-6300Hz and 1600-6300Hz respectively. The results are as follows: Figure 3 and Figure 4 shown.
[0039] Comparative Example 2
[0040] This comparative example provides an application of aerogel in synergistic magnetic field in noise reduction: the aerogel is placed in a magnetic field to absorb sound waves.
[0041] The preparation method of aerogel comprises the following steps:
[0042] Step 1: Take 1g of aramid fiber, 1g of potassium hydroxide and 2g of deionized water, add them into 500ml of dimethyl sulfoxide, stir for one week to decompose the aramid fiber to form aramid nanofibers, and wash them repeatedly with deionized water to obtain aramid nanofibers. Then disperse the aramid nanofibers in deionized water to obtain a 2mg / g aramid nanofiber solution.
[0043] Step 2: Vacuum filter 160 g of aramid nanofiber solution to 32 g, fill it into a prefabricated square mold of 4 cm*4 cm*2 cm, and move it to a refrigerator and freeze it at -18°C for 24 hours.
[0044] The frozen aramid nanofiber solution was transferred to a vacuum freeze dryer for freeze drying at a cold well temperature of -80°C for 7 days, and finally aramid nanofiber aerogel was obtained.
[0045] Sound wave absorption performance test: Add the following on the outside of the four-channel digital signal acquisition system and the impedance tube: Figure 2 The magnetic field generating device was used to measure the sound absorption performance at 1600-6300 Hz, and the magnetic field intensity was 0.2T.
[0046] Sound wave absorption performance test: Add the following on the outside of the four-channel digital signal acquisition system and the impedance tube: Figure 2 The magnetic field generating device was used to measure the sound absorption performance at 1600-6300Hz, with a magnetic field intensity of 0.2T. The results are as follows Figure 5 shown.
[0047] Comparative Example 3
[0048] This comparative example provides an application of aerogel in noise reduction: the aerogel is directly used for sound wave absorption. The preparation method of the aerogel is the same as that of comparative example 2.
[0049] Sound wave absorption performance test: Using a four-channel digital signal acquisition system and an impedance tube, the sound absorption performance was measured at 250-6300Hz and 1600-6300Hz respectively. The results are as follows: Figure 3 and Figure 5 shown.
[0050] Depend on Figure 3 It can be seen that within the test range, the aramid nanofiber / magnetic particle mixed aerogel prepared in Comparative Example 1 has a better sound absorption effect than that in Comparative Example 3. The improvement in the sound absorption effect mainly comes from the microscopic rough surface in the aramid nanofiber / magnetic particle mixed aerogel in Comparative Example 1. When sound waves enter the sound-absorbing material, they will cause the vibration of the internal air. The vibrating air at the pore wall and the skeleton will show an obvious fluid viscosity effect, and then there will be a loss phenomenon of sound energy being converted into heat energy. Compared with the smooth microscopic surface of Comparative Example 3, the rough microscopic surface of the material in Comparative Example 1 has a stronger viscous loss mechanism. Therefore, Comparative Example 1 has a more excellent sound absorption performance.
[0051] Depend on Figure 4 and Figure 5 It can be seen that within the test range, the presence or absence of a magnetic field has a significant effect on the sound absorption performance of the aramid nanofiber / magnetic particle hybrid aerogel, but has a weak effect on the sound absorption performance of the aramid nanofiber aerogel. The regulation of the sound absorption performance of the aramid nanofiber / magnetic particle hybrid aerogel by the magnetic field comes from the magnetic particles in the aerogel material. When the magnetic field is applied, the magnetic micro-skeleton of the aramid nanofiber / magnetic particle hybrid aerogel will deform due to the magnetic response to the magnetic field, and then there will be a significant change in the sound absorption performance in the research frequency band of 1600-6300Hz.
[0052] Furthermore, the effect of magnetic field on the microstructure of aramid nanofiber / magnetic particle hybrid aerogel and aramid nanofiber aerogel was observed by optical microscopy. Figure 6 and Figure 7 As shown. Figure 6 As shown in the figure, under the condition of magnetic field, the microstructure of aramid nanofiber / magnetic particle hybrid aerogel shows skeleton shrinkage phenomenon, which will lead to the reduction of microscopic pore size of aramid nanofiber / magnetic particle hybrid aerogel, thereby achieving the absorption of broadband sound waves. The deformation diagram is shown in Figure 8 As shown. Figure 7 As shown in the figure, the microstructure of the aramid nanofiber aerogel did not change under the condition of a magnetic field.
[0053] In the present invention, unless otherwise specified, the scientific and technical terms used herein have the meanings commonly understood by those skilled in the art. In addition, the reagents, materials and operating procedures used herein are reagents, materials and conventional procedures widely used in the corresponding fields.
[0054] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. Application of a controllable broadband sound-absorbing aerogel in noise reduction, characterized in that: The broadband sound-absorbing aerogel is placed in a magnetic field to absorb sound waves; The method for preparing the broadband sound-absorbing aerogel comprises the following steps: Step 1: Mixing and stirring the aramid nanofiber dispersion and the magnetic particles to obtain an aramid nanofiber / magnetic particle mixed solution; Step 2: freeze-drying the aramid nanofiber / magnetic particle mixed solution to obtain an aramid nanofiber / magnetic particle mixed aerogel.
2. The use of the adjustable broadband sound-absorbing aerogel in noise reduction according to claim 1, characterized in that: The intensity of the magnetic field is 0.1-2T.
3. The use of the adjustable broadband sound-absorbing aerogel in noise reduction according to claim 1, characterized in that: The magnetic field is generated by a copper coil through which a DC power source is passed.
4. The use of the adjustable broadband sound-absorbing aerogel in noise reduction according to claim 1, characterized in that: In step 1, the preparation method of the aramid nanofiber dispersion is: aramid fibers, potassium hydroxide, deionized water and dimethyl sulfoxide are mixed and stirred for 6 to 8 days to crack the aramid fibers to obtain aramid nanofibers; and then the aramid nanofibers are dispersed in deionized water to obtain the aramid nanofiber dispersion.
5. The use of the adjustable broadband sound-absorbing aerogel in noise reduction according to claim 4 is characterized in that: In the preparation of the aramid nanofiber dispersion, the usage ratio of aramid fiber, potassium hydroxide, deionized water and dimethyl sulfoxide is 0.5-2g: 0.5-2g: 1-3g: 300-800ml.
6. The use of the adjustable broadband sound-absorbing aerogel in noise reduction according to claim 1, characterized in that: In step 1, the magnetic particles are ferrite, carbonyl iron powder or iron-silicon alloy.
7. The use of the adjustable broadband sound-absorbing aerogel in noise reduction according to claim 1, characterized in that: In step 1, the concentration of the aramid nanofiber dispersion is 1-3 mg / g; the mass ratio of the aramid nanofiber dispersion to the magnetic particles is 100-200:0.3-1.
0.
8. The use of the adjustable broadband sound-absorbing aerogel in noise reduction according to claim 1, characterized in that: In step 1, the stirring time is 3 to 5 hours and the rotation speed is 1000 r / min.
9. The use of the adjustable broadband sound-absorbing aerogel in noise reduction according to claim 1, characterized in that: In step 2, the freeze-drying temperature is -10 to -80°C and the time is 5 to 7 days.
10. The use of the adjustable broadband sound-absorbing aerogel in noise reduction according to claim 1, characterized in that: In step 2, before freeze drying, the aramid nanofiber / magnetic particle mixed solution is first frozen at -18 to -80°C for 24 hours.
Citation Information
Patent Citations
Preparation method of aerogel with electromagnetic shielding and sound absorption functions
CN114920978A
Sound absorption system based on acoustic metamaterial and regulation and control method thereof
CN116758887A